Everyone Orthodox to Themselves: John Locke and His American Students on Religion and Liberal Society by John Colman - Haines, Benjamin (Locke Studies, 2024)
A review of John Colman’s recent book Everyone Orthodox to Themselves: John Locke and His American Students on Religion and Liberal Society (Lawrence: University of Kansas Press, 2023)